2020
DOI: 10.3390/ijms21175990
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Cytokine Levels Differ by HPV Status and Change Treatment-Dependently in Patients with Head and Neck Squamous Cell Carcinoma

Abstract: Cytokines and immune mediators play an important role in the communication between immune cells guiding their response to infectious diseases or cancer. In this study, a comprehensive longitudinal analysis of serum cytokines and immune mediators in head and neck squamous cell carcinoma (HNSCC) patients was performed. In a prospective, non-interventional, longitudinal study, blood samples from 22 HNSCC patients were taken at defined time points (TP) before, during, and every 3 months after completion of (chemo)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This notion is supported by increased levels of mainly inhibitory cytokines in the peripheral blood (IRECT‐001: IL10, IRECT‐006 and IRECT‐018: IL4) at the time of recurrent disease (data not shown). In some patients, a sharp increase of High Mobility Group Box 1 (IRECT‐001, ‐013, ‐017, ‐018), known to act immunosuppressively on T cells, 42,43 was measured around the time of disease recurrence as previously published 9 . A recently published study using single cell RNA sequencing of peripheral and intratumoral lymphocytes indicates that the coexpression of LAG3 and TIM3 inhibits CD4 T cells to develop into T follicular helper cells and instead may promote development into a suppressive phenotype 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is supported by increased levels of mainly inhibitory cytokines in the peripheral blood (IRECT‐001: IL10, IRECT‐006 and IRECT‐018: IL4) at the time of recurrent disease (data not shown). In some patients, a sharp increase of High Mobility Group Box 1 (IRECT‐001, ‐013, ‐017, ‐018), known to act immunosuppressively on T cells, 42,43 was measured around the time of disease recurrence as previously published 9 . A recently published study using single cell RNA sequencing of peripheral and intratumoral lymphocytes indicates that the coexpression of LAG3 and TIM3 inhibits CD4 T cells to develop into T follicular helper cells and instead may promote development into a suppressive phenotype 24 …”
Section: Discussionmentioning
confidence: 99%
“…Within the prospective noninterventional clinical study titled “Immune Response Evaluation to Curative conventional Therapy (IRECT)” (NCT03053661), systematic immune monitoring was performed longitudinally during conventional treatment of locoregionally advanced HNSCC 9 . Here, we present flow cytometry data assessing nine ICM on peripheral T and B cells from patients harvested during the course of curative treatment and follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine levels in HNC have been studied in several previous works using different analytical techniques [ 16 , 54 ]. Dickinson et al used mass spectrometry to differentiate proteins in sera from HPV-positive and HPV-negative patients, and found that three proteins were expressed differently [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors indicate a low specificity. In this study, HMGB1 was measured only once during radiotherapy [ 36 ]. To further evaluate the potential of this biomarker in patients with HNSCC, we investigated HMGB1 in weekly sampling during definitive radiochemotherapy and during follow-up in a homogenous cohort of patients undergoing curative definitive radiochemotherapy for locally advanced HNSCC.…”
Section: Discussionmentioning
confidence: 99%